Samuel Clarke's Lives and husbands' remembrances of their wives. Issue 4 (8th August 2019) - Anselment, Raymond A.
ABSTRACT: Among the narratives of eminent divines and Christian worthies that Samuel Clarke derived from published sources and included in his many publications are the lives of fifteen early modern women, three of them written by their husbands. Humphrey Gunter's funeral memorial of his wife Mary, Samuel Clarke's life of Katherine, and Richard Baxter's of Margaret have a personal immediacy and an affectionate detail often absent from the other biographies. In the contexts of both the original publications and Clarke's texts, their depictions of spousal relationships reflect the tension between traditional commemoration and individual expression apparent in seventeenth-century narratives of women's lives. The bonds each husband recalls celebrate the virtuous wife, though none of the recollections is as forthright as Baxter's insightful recognition of Margaret's complex character and her significant role in their marriage.